2016
DOI: 10.1515/intag-2015-0074
|View full text |Cite
|
Sign up to set email alerts
|

Expansion in chickpea (Cicer arietinum L.) seed during soaking and cooking

Abstract: A b s t r a c t. The linear and volumetric expansion of chickpea seeds during water absorption at 20, 30, 50, 70, 85 and 100°C was studied. Length, width and thickness of chickpea seeds linearly increased with the increase in moisture content at all temperatures studied, where the greatest increase was found in length. Two different mathematical approaches were used for the determination of the expansion coefficients. The plots of the both linear and volumetric expansion coefficients versus temperature exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
(41 reference statements)
2
5
0
Order By: Relevance
“…), respectively. Similar trend was observed for other grains as green wheat (Al‐Mahasneh & Rababah, 2007), chickpeas (Sayar, Turhan, & Köksel, 2016), faba beans (Altuntas & Yildiz, 2007), and sorghum (Gely & Pagano, 2017).…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…), respectively. Similar trend was observed for other grains as green wheat (Al‐Mahasneh & Rababah, 2007), chickpeas (Sayar, Turhan, & Köksel, 2016), faba beans (Altuntas & Yildiz, 2007), and sorghum (Gely & Pagano, 2017).…”
Section: Resultssupporting
confidence: 69%
“…3 | RESULTS AND DISCUSSION (Sayar, Turhan, & Köksel, 2016), faba beans (Altuntas & Yildiz, 2007), and sorghum (Gely & Pagano, 2017).…”
Section: Physical Properties Of the Grains Bedmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Sayar et al [ 43 ] utilized two approaches to model the linear (length, width, and thickness) and volumetric expansion of chickpea seeds as a function of water uptake during soaking at different temperatures (20–100 °C). The first approach was based on the experimental correlation between volume variation and water absorption of chickpeas during soaking, expressed as follows: where V is the volume of chickpea at time t , and V 0 its initial volume; M is the weight of chickpea at time t , while M 0 its initial weight; ρ w is the density of water, and λ is the volumetric expansion coefficient.…”
Section: Applications In Various Products/processesmentioning
confidence: 99%
“…In this case, different values of the expansion coefficient ( β ) were obtained by using volume, length, width and thickness variation of chickpeas, indicating anisotropic swelling. Furthermore, Sayar et al [ 43 ] analyzed the variation of different expansion coefficients with temperature: Overall, all coefficients decreased linearly in the range of 20–50 °C, and then remained constant for 70–100 °C. The authors indicated that starch gelatinization occurring at around 60 °C would explain this behavior in swelling of chickpeas.…”
Section: Applications In Various Products/processesmentioning
confidence: 99%